Impact of the COVID-19 Lockdown on Ophthalmological Assistance in the Emergency Department at a Spanish Primary Level Hospital - Julio González-Martín-Moro; Elena Guzmán-Almagro; Carlos Izquierdo Rodríguez; Ana Fernández Hortelano; Inmaculada Lozano Escobar; Fernando Gómez Sanz; Inés Contreras (Journal of Ophthalmology)
Purpose. To analyze the changes in ophthalmological emergencies during the COVID-19 pandemic lockdown at a Spanish primary level hospital. Methods. The number and type of emergencies attended in the emergency department of Hospital Universitario del Henares between March 10 and August 31, 2020 (COVID-19 cohort) were compared with the emergencies attended during the same period of 2019 (pre-COVID-19 cohort). Data on the diagnosis, patient age, and gender was retrospectively collected from the electronic medical records of the hospital. The different diagnoses were organized into “clusters,” which include those conditions that affect the same ocular tissue and that have similar clinical expression. Results. The number of ophthalmological emergencies during the study period was 841, compared to 1343 during the same month of 2019, which represents a reduction of 37.4%. The percentage reduction in each cluster was as follows: conjunctiva (−65.4%), cornea (−35.8%), uveitis (−3.6%), eyelid and orbital and lacrimal (−35.5%), strabismus (−60%), neuro-ophthalmology (−11.8%), retina (−10.6%), cataract (+16.4%), glaucoma (−37%), and miscellaneous (−45.1%). The number of people seen with viral conjunctivitis decreased by −87.1% compared to 2019. Patients with complications due to conjunctivitis also decreased: patients with pseudomembranes dropped from 16 to 4 cases and patients with corneal subepithelial infiltrates from 9 to 3 cases. Conclusions. Most diagnostic clusters showed a similar decrease. Clusters that included vision-threating conditions (retina, neuro-ophthalmology, and uveitis) remained mostly stable. During the COVID-19 lockdown, the diagnosis of adenoviral conjunctivitis decreased nearly 10 times. This fact may represent a decrease in the transmission of these infections.